Intraabdominal dissemination of porocarcinoma; A case report. (September 2022) - Misso, Kennedy; Shadrack, Mathayo; Ntakarutimana, Venant; Nkya, Gilbert; Tarmohamed, Murad; Chilonga, Kondo
Abstract: Introduction: Porocarcinoma is a rare malignancy of dermal sweat glands commonly diagnosed in the seventh decade of life. It frequently evolves from a de novo benign poroma. These tumors present as a mass/nodule, ulcer, papule, or wart. Difficult to differentiate from other cutaneous lesions. Intraperitoneal invasion is scantly reported in the literature. Case presentation: The authors present a case of a fifty-year-old female patient with a rare cancer of the dermal sweat glands in an unusual location and infiltration into the abdominal cavity, leading to intraperitoneal seedlings. Discussion: Tumors of the sweat gland are rare and difficult to diagnose, often misdiagnosed as granuloma, squamous cell tumors, or warts. Surgical excision and Mohs micrographic surgery are mainstay treatment modalities in the early stages. Our patient was managed elsewhere with a diagnosis of granuloma. She was referred with a recurrence of the abdominal lesion. An appropriate diagnosis of porocarcinoma was made while she had an extensive intraperitoneal invasion and seedlings. We postulate that the previous abdominal incision had disseminated porocarcinoma cells into the abdominal cavity, causing extensive intraperitoneal dissemination. Conclusion: Because it is rare and difficult to diagnose, there is a considerable knowledge gap in the early accurate diagnosis and appropriate management of porocarcinoma. This causes a delay in establishing a diagnosis and profoundly impacts treatment outcomes. Highlights: Eccrine porocarcinoma is a rare diagnosis of cutaneous malignancy. Early diagnosis and appropriate surgical treatment are the cornerstones of improving survival. It is often misdiagnosed as granuloma, squamous cell carcinoma, or viral warts.